Distinct DNA methylation patterns associated with active and inactive centromeres of the maize B chromosome - Koo, Dal-Hoe; Han, Fangpu; Birchler, James A.; Jiang, Jiming (Genome Research, 2011)
Centromeres are determined by poorly understood epigenetic mechanisms. Centromeres can be activated or inactivated without changing the underlying DNA sequences. However, virtually nothing is known about the epigenetic transition of a centromere from an active to an inactive state because of the lack of examples of the same centromere exhibiting alternative forms and being distinguishable from other centromeres. The centromere of the supernumerary B chromosome of maize provides such an opportunity because its functional core can be cytologically tracked, and an inactive version of the centromere is available. We developed a DNA fiber-based technique that can be used to assess the levels of cytosine methylation associated with repetitive DNA sequences. We report that DNA sequences in the normal B centromere exhibit hypomethylation. This methylation pattern is not affected by the genetic background or structural rearrangement of the B chromosome, but is slightly changed when the B chromosome is transferred to oat as an addition chromosome. In contrast, an inactive version of this same centromere exhibits hypermethylation, indicating that the inactive centromere was modified into a different epigenetic state at the DNA level.